2003
DOI: 10.1074/jbc.m212469200
|View full text |Cite
|
Sign up to set email alerts
|

Oligomerization of the Murine Fatty Acid Transport Protein 1

Abstract: The 63-kDa murine fatty acid transport protein 1 (FATP1) was cloned on the basis of its ability to augment fatty acid import when overexpressed in mammalian cells. The membrane topology of this integral plasma membrane protein does not resemble that of polytopic membrane transporters for other substrates. Western blot analysis of 3T3-L1 adipocytes that natively express FATP1 demonstrate a prominent 130-kDa species as well as the expected 63-kDa FATP1, suggesting that this protein may participate in a cell surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 26 publications
5
29
0
Order By: Relevance
“…Previously, we published results indicating that FATP1 homodimerization plays a role in fatty acid uptake function (19). In this study, we observed coimmunoprecipitation between differently epitope-tagged forms of FATP1 and ACSL1 in 3T3-L1 adipocytes.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Previously, we published results indicating that FATP1 homodimerization plays a role in fatty acid uptake function (19). In this study, we observed coimmunoprecipitation between differently epitope-tagged forms of FATP1 and ACSL1 in 3T3-L1 adipocytes.…”
Section: Discussionsupporting
confidence: 59%
“…Previously, we showed that FATP1 forms homodimers and that dimerization plays a functional role in cellular fatty acid import (19). Thus, we tested whether ACSL1 forms an oligomeric complex with more than one molecule of FATP1.…”
Section: Fatp1 and Acsl1 Coimmunoprecipitate In 3t3-l1 Adipocytesmentioning
confidence: 99%
“…These data are consistent with the proposal that this motif contributes to fatty acid transport. Several FATPs are localized, at least in part, to the plasma membrane further supporting their functional role in fatty acid transport [7,9,11,[23][24][25]. The transmembrane domains within the FATPs are amino-terminal proximal; one transmembrane domain has been identified in FATP1 [23] while two have been identified in Fat1p [26].…”
Section: Introductionmentioning
confidence: 95%
“…Whereas it is highly speculative that the first 185 amino acids encoded by exons 1 and 2 would present a peptide with biological activity, it is worthwhile noting that this region is homologous to fragments of FATP1 that would include the entire extracellular N terminus, the transmembrane region, and cytoplasmic membraneassociated sequences (38). Because FATPs may be multifunctional proteins with separable residues involved in LCFA transport and activation (39), the hypothetical fusion proteins could retain some aspects of FATP4 function, such as LCFA transport, or interaction with other proteins, for instance longchain acyl-CoA synthetases (40) or other FATPs (19). Although the causes of neonatal mortality, described by Moulson et al (30) and Herrmann et al (22), may differ from the embryonic death described in this article, both lethalities ultimately underscore the importance of FATP4-mediated LCFA uptake/ activation for normal physiology.…”
Section: Table IIImentioning
confidence: 99%
“…The AMP-binding motive in FATP1 mediates ATP binding and is required for LCFA uptake, since mutations within this motif abolish uptake activity (17,18). Oligomerization also seems to be required for transport function, because co-expression of non-functional FATP1 mutants with wild-type FATP1 resulted in dominant negative inhibition of transport (19). Based on the finding that both long-chain and very long-chain acyl-CoA synthetase activities are increased in lysates from FATP overexpressing cells (20) and in partially purified FATP1 and -4 precipitates (21,22), it has been suggested that FATPs are acyl-CoA ligases that directly couple LCFA uptake with CoA activation, thereby trapping fatty acids inside the cell.…”
mentioning
confidence: 99%